Exceptional 20th Century Shifts in Deep-Sea Ecosystems Are Spatially Heterogeneous and Associated With Local Surface Ocean Variability - O’Brien, Charlotte L.; Spooner, Peter T.; Wharton, Jack H.; Papachristopoulou, Eirini; Dutton, Nicolas; Fairman, David; Garratt, Rebecca; Li, Tianying; Pallottino, Francesco; Stringer, Fiona; Thornalley, David J. R. (Frontiers in Marine Science, 2021)
Traditionally, deep-sea ecosystems have been considered to be insulated from the effects of modern climate change, but with the recognition of the importance of food supply from the surface ocean and deep-sea currents to sustaining these systems, the potential for rapid response of benthic systems to climate change is gaining increasing attention. However, very few ecological time-series exist for the deep ocean covering the twentieth century. Benthic responses to past climate change have been well-documented using marine sediment cores on glacial-interglacial timescales, and ocean sediments have also begun to reveal that planktic species assemblages are already being influenced by global warming. Here, we use benthic foraminifera found in mid-latitude and subpolar North Atlantic sediment cores to show that, in locations beneath areas of major surface water change, benthic ecosystems have also changed significantly over the last 150 years. The maximum benthic response occurs in areas which have seen large changes in surface circulation, temperature and/or productivity. We infer that the observed surface-deep ocean coupling is due to changes in the supply of organic matter exported from the surface ocean and delivered to the seafloor. The local-to-regional scale nature of these changes highlights that accurate projections of changes in deep-sea ecosystems will require (1) increased spatial coverage of deep-sea proxy records and, (2) models capable of adequately resolving these relatively small-scale oceanographic features.